Structural Transformations and Spin‐Crossover in [FeL2]2+ Salts (L=4‐{tert‐Butylsulfanyl}‐2, 6‐dipyrazol‐1‐ylpyridine): The Influence of Bulky Ligand Substituents. Issue 6 (23rd December 2020) - Kulmaczewski, Rafal; Bamiduro, Faith; Shahid, Namrah; Cespedes, Oscar; Halcrow, Malcolm A.
Abstract: 4‐( tert ‐Butylsulfanyl)‐2, 6‐di(pyrazol‐1‐yl)pyridine ( L ) was obtained in low yield from a one‐pot reaction of 2, 4, 6‐trifluoropyridine with 2‐methylpropane‐2‐thiolate and sodium pyrazolate in a 1:1:2 ratio. The materials [Fe L 2 ][BF4 ]2 ⋅solv (1[BF4 ]2 ⋅solv) and [Fe L 2 ][ClO4 ]2 ⋅solv (1[ClO4 ]2 ⋅solv; solv=MeNO2, MeCN or Me2 CO) exhibit a variety of structures and spin‐state behaviors including thermal spin‐crossover (SCO). Solvent loss on heating 1[BF4 ]2 ⋅ x  MeNO2 ( x ≈2.3) occurs in two steps. The intermediate phase exhibits hysteretic SCO around 250 K, involving a "reverse‐SCO" step in its warming cycle at a scan rate of 5 K min −1 . The reverse‐SCO is not observed in a slower 1 K min −1 measurement, however, confirming its kinetic nature. The final product [Fe L 2 ][BF4 ]2 ⋅0.75 MeNO2 was crystallographically characterized, and shows abrupt but incomplete SCO at 172 K which correlates with disorder of an L ligand. The asymmetric unit of 1[BF4 ]2 ⋅ y  Me2 CO ( y ≈1.6) contains five unique complex molecules, four of which undergo gradual SCO in at least two discrete steps. Low‐spin 1[ClO4 ]2 ⋅0.5 Me2 CO is not isostructural with its BF4 − congener, and undergoes single‐crystal‐to‐single‐crystal solvent loss with a tripling of the crystallographic unit cell volume, while retaining the P 1 ‾ space group. Three other solvate salts undergo gradual thermal SCO. Two of these are isomorphous at room temperature, but transform to different low‐temperature phases when the materials are fully low‐spin. Abstract : Desolvation of [Fe L 2 ][BF4 ]2 ⋅ x  MeNO2 occurs via an intermediate phase, which exhibits hysteretic spin‐crossover (SCO) with a reverse step in its warming branch when measured at a faster scan rate. Incomplete SCO in the final product phase reflects disorder of an L ligand. [Fe L 2 ][BF4 ]2 ⋅ y  Me2 CO contains five complex cations per asymmetric unit, four of which undergo gradual SCO in at least two discrete steps.